Society for Immunotherapy of Cancer (SITC) consensus definitions for immune checkpoint inhibitor-associated immune-related adverse events (irAEs) terminology. Issue 3 (31st March 2023) - Naidoo, Jarushka; Murphy, Catherine; Atkins, Michael B; Brahmer, Julie R; Champiat, Stephane; Feltquate, David; Krug, Lee M; Moslehi, Javid; Pietanza, M Catherine; Riemer, Joanne; Robert, Caroline; Sharon, Elad; et al.
Abstract : Immune-related adverse events (irAEs) associated with immune checkpoint inhibitor (ICI) therapy may vary substantially in their clinical presentation, including natural history, outcomes to treatment, and patterns. The application of clinical guidelines for irAE management can be challenging for practitioners due to a lack of common or consistently applied terminology. Furthermore, given the growing body of clinical experience and published data on irAEs, there is a greater appreciation for the heterogeneous natural histories, responses to treatment, and patterns of these toxicities, which is not currently reflected in irAE guidelines. Furthermore, there are no prospective trial data to inform the management of the distinct presentations of irAEs. Recognizing a need for uniform terminology for the natural history, response to treatment, and patterns of irAEs, the Society for Immunotherapy of Cancer (SITC) convened a consensus panel composed of leading international experts from academic medicine, industry, and regulatory agencies. Using a modified Delphi consensus process, the expert panel developed clinical definitions for irAE terminology used in the literature, encompassing terms related to irAE natural history (ie, re-emergent, chronic active, chronic inactive, delayed/late onset), response to treatment (ie, steroid unresponsive, steroid dependent), and patterns (ie, multisystem irAEs). SITC developed these definitions to support the adoption of a standardized vocabulary for irAEs, which will have implications for the uniform application of irAE clinical practice guidelines and to enable future irAE clinical trials.